Quality and safety of buffalo milk from Malaysian farms: physicochemical properties, aflatoxin M1 and antibiotic residues - Ibrahim, Aimie Syahirah; Sukor, Rashidah; Meor Hussin, Anis Shobirin; Mohsin, Aliah Zannierah (Cambridge University Press, 2026)
This Research Communication reports the physicochemical properties, aflatoxin levels and antibiotic residues in buffalo milk. The milk and feed samples were collected from nine farms in Peninsular Malaysia, with the lactation stage studied in one farm. Buffalo milk composition varied across farms; Petaling Jaya showed high fat and total solids but low protein and solids non-fat (SNF), while Jitra 1 and Seberang Perai 2 exhibited higher protein, casein and SNF. Langkawi and Hulu Langat had higher moisture, ash and lactose levels. Early and late lactation were linked to higher protein and casein. Aflatoxin B1 in feed was undetectable; however, aflatoxin M1, amoxicillin and oxytetracycline were present in milk but below the regulatory limits. These findings indicate that current on-farm management practices are effective in ensuring the safety and quality of buffalo milk, while continuous monitoring remains crucial.